2015
DOI: 10.1007/s12010-015-1931-5
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Properties of Fish Protein Hydrolysates Prepared from Cod Protein Hydrolysate by Bacillus sp.

Abstract: Fermentative protein hydrolysates (FPH) were prepared with a proteolytic bacterium, Bacillus strain exhibiting high proteolytic activity. Three FPH with 1, 2, and 4 % of cod protein hydrolysate (CPH) and 0.5 % of yeast extract in the culture were prepared. The yields achieved varied between 30 and 58 % based on protein content. A general decrease of leucine, isoleucine, valine, alanine, arginine, threonine, proline, and glutamic acid was observed. All FPHs showed higher reducing power and DPPH radical scavengi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…Lactobacillus plantarum fermented alone can increase reducing power and ABTS + and DPPH radical scavenging activities [21]. Moreover, Bacillus sp.fermented cod protein hydrolysate can increase reducing power and DPPH radical scavenging activity [22]. In the present study, the DPPH and ABTS + radical scavenging activities, and relative reducing powers, of F3 and F6 were significantly higher than those in FB.…”
Section: Discussionsupporting
confidence: 39%
“…Lactobacillus plantarum fermented alone can increase reducing power and ABTS + and DPPH radical scavenging activities [21]. Moreover, Bacillus sp.fermented cod protein hydrolysate can increase reducing power and DPPH radical scavenging activity [22]. In the present study, the DPPH and ABTS + radical scavenging activities, and relative reducing powers, of F3 and F6 were significantly higher than those in FB.…”
Section: Discussionsupporting
confidence: 39%
“…Fermentation is a cost-effective method for generating bioactive peptides and food-grade proteins hydrolysates through the action of microorganisms (Ozyurt et al, 2017). Microbial fermentation has been reported as an ideal method to produce bioactive peptides at the industrial level as it is economically feasible and more eco-friendly than the enzymatic method (Godinho et al, 2015;Jemil et al, 2016). Moreover, fermentation plays a significant role in improving the organoleptic and physicochemical properties of products (Najafian and Babji, 2018).…”
Section: Hydrolysis Of Protein Concentratesmentioning
confidence: 99%
“…Lactic acid bacteria are frequently used to produce antioxidant peptides from different protein sources. Several studies reported the production of antioxidant protein hydrolysates and peptides from the protein of different plant, animal and marine sources, and their industrial by-products fermented by Bacillus subtilis A26, Bacillus amyloliquefaciens An6, Streptococcus spp., Lactobacillus brevis, Lactobacillus plantarum, Pediococcus acidilactici and Enterococcus gallinarum (Godinho et al, 2015;Jemil et al, 2016;Najafian and Babji, 2018;Ozyurt et al, 2017;Rajendran et al, 2018). Najafian and Salam (2018) identified two new antioxidant peptides, Ala-Ile-Pro-Pro-His-Pro-Tyr-Pro and Ile-Ala-Glu-Val-Phe-Leu-Ile-Tre-Asp-Pro-Lys, from Loma fish protein hydrolysate fermented by Lactobacillus plantarum IFRPD P15.…”
Section: Hydrolysis Of Protein Concentratesmentioning
confidence: 99%
See 1 more Smart Citation
“…That is, protein hydrolysates may form an oil-in-water emulsion more easily than intact proteins because of their efficiency in absorbing oil. The reported dated (Hebishy et al, 2015) have made the researchers upgrade the protein-to-protein hydrolysates in order to increase the emulsifying capacity of raw materials, regardless of the source of raw material is either fish protein derived from something such as cod (Godinho et al, 2016) or plant-based protein derived from something such as soy . The results in Figure 3 illustrate that as the processing time increased, the emulsifying capacity of the protein hydrolysates decreased (from 150 m 2 g −1 at 5 min to 30 m 2 g −1 at 120 min).…”
Section: Emulsifying Capacity and Stabilitymentioning
confidence: 99%